SUPPORTING URBAN POOR FACING CLIMATE CHANGE: CREATING EFFECTIVE ADAPTATION MESSAGES (MENDUKUNG MASYARAKAT MISKIN KOTA MENGHADAPI PERUBAHAN IKLIM: MENYUSUN PESAN ADAPTASI YANG EFEKTIF) - Syarifah Aini Dalimunthe (Jurnal Kependudukan Indonesia, 2014)
Government, international agencies, civic society, and media organizations in Indonesia have communicated climate change to people. The examples are communication campaigns focusing on “green” activities, such as bike to work, car-free days, and energy-efficient buildings. One simple question arises in the practice: could these types of communication reach and provide benefits for the most vulnerable group? This paper offers an overview of urban poor audience needs of information, particularly on what media they use, who they talk to and trust, and how they would like Information delivered to them. As an exercise in crafting messages, women in urban poor will be put as the priority audience. This group falls into the struggling segment (41%). They are experiencing the most impact and cannot take much action. The struggling is willing to make changes, but lack of information and support prevents them from taking action. By understanding this sort of information, it will support delivering effective climate change adaptation messages. The methods included in this research are in-depth interviews, focus group discussion, and survey to 928 urban poor in Indonesia.